Fracture resistance and the mode of failure produced in metal-free crowns cemented onto zirconia abutments in dental implants - Agustín-Panadero, Rubén; Serra-Pastor, Blanca; Roig-Vanaclocha, Ana; Fons-Font, Antonio; Solá-Ruiz, María Fernanda (PloS one, 2019)
The purpose of the investigation was to analyze fracture resistance and mode of failure of zirconium oxide (zirconia) abutments placed on dental implants bearing crowns of different esthetic materials: zirconia, lithium disilicate (LDS), and nano-ceramic resin, for replacing single teeth in the anterior sector. Eighty implant-abutment-crown units were divided into four groups: Group T-MC (control): 20 metal-ceramic crowns cemented onto titanium abutments; Group Z-Z: 20 zirconia crowns on zirconia abutments; Group Z-LD: 20 lithium disilicate crowns on zirconia abutments; and Group Z-NCR: 20 nano-ceramic resin crowns on zirconia abutments. Specimens underwent a fatiguing process (dynamic loading and thermocycling), followed by static loading to evaluate mechanical fracture resistance, and the mode of failure produced. Mean fracture resistance values were: Control Group T-MC, 575.85±120.01 N; Group Z-Z 459.64±66.52 N; Group Z-LD, 531.77±34.10 N; and Group Z-NCR, 587.05±59.27 N. In Group T-MC, fracture occurred in the prosthetic fixing screw in 100% of specimens. In Group Z-Z, 80% of fractures occurred in the fixing screw, 15% in the abutment, and 5% in the abutment and crown. In Group Z-LD, 60% of fractures were produced in the fixing screw and 40% in the abutment. In Group Z-NCR, 70% of fractures were produced in the fixing screw and 30% in the abutment. All the abutments and crowns analyzed have the potential to withstand the physiological occlusal forces to which they would be subject in the anterior region. Lithium disilicate and nano-ceramic resin crowns cemented onto zirconia abutments are a good restoration alternative for single implants in the anterior sector.